Designing Digital Gamification Literacy For EFL teachers - Joyonegoro, Dinar Auliarahman; Agustina, Eliasanti (Journal of Applied Linguistics and English Education, 2025)
This research aims to design digital gamification literacy for English as a Foreign Language (EFL) teachers, particularly in the context of the Merdeka Curriculum in Indonesia. In the current digital era, gamification has emerged as an innovative approach to enhance student motivation, engagement, and learning outcomes. However, many teachers still face obstacles in adopting this strategy, such as a lack of understanding, training, and limited access to technology. This study employs an explanatory mixed-method approach, involving 20 lecturers from the English Education study program in a quantitative survey and 3 of them in qualitative interviews. The research results show that although the majority of respondents are accustomed to using digital technology, only a small fraction actively apply gamification in their teaching. The main obstacles identified include time constraints, lack of training, and gaps in technology access. On the other hand, the participants showed a high interest in gamification training and recognized its positive potential in enhancing student-centered learning. This study recommends the development of practice communities, experiential training, and the provision of structured digital resources as strategic steps to strengthen digital gamification literacy among EFL teachers.